سنة حكم جديدة من عصر الملك " أنليل باني " في ضوء نص توزيع مسماري غير منشور - نايف, سمراء حميد (مجلة دراسات في التاريخ والآثار, 2024)
The study of Date formulas is one of the most important studiesthat shed the light on the history of Mesopotamia, as it is full and rich in information, till it became a reliable information source that leads us to solve all the problems within the periods it represents.